2013
DOI: 10.1016/j.bbamcr.2013.06.019
|View full text |Cite|
|
Sign up to set email alerts
|

Cyclical strain modulates metalloprotease and matrix gene expression in human tenocytes via activation of TGFβ

Abstract: Tendinopathies are a range of diseases characterised by degeneration and chronic tendon pain and represent a significant cause of morbidity. Relatively little is known about the underlying mechanisms; however onset is often associated with physical activity. A number of molecular changes have been documented in tendinopathy such as a decrease in overall collagen content, increased extracellular matrix turnover and protease activity. Metalloproteinases are involved in the homeostasis of the extracellular matrix… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
49
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(50 citation statements)
references
References 97 publications
1
49
0
Order By: Relevance
“…A less active metabolic response from the tenocytes from tendinopathic tendon was also observed by Jones et al, when these same cell populations were subject to 5% cyclic strain at 1 Hz in collagen gels using a flexcell system. Both of these studies adopted 3D models, and it is unclear how this may relate to the 2D response.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…A less active metabolic response from the tenocytes from tendinopathic tendon was also observed by Jones et al, when these same cell populations were subject to 5% cyclic strain at 1 Hz in collagen gels using a flexcell system. Both of these studies adopted 3D models, and it is unclear how this may relate to the 2D response.…”
Section: Discussionsupporting
confidence: 65%
“…However, previous studies have demonstrated that housing cells in a 3D environment can provide a more physiologically relevant cell environment as a basis for such investigations . For example, using 3D collagen gels, human Achilles tenocytes have been reported to express increases in ADAMTS2/4/16, MMP24, TIMP3, and type I collagen gene expression after 24‐ or 48‐hours loading …”
Section: Introductionmentioning
confidence: 99%
“…3D loading is superior to 2D loading as a result of its greater resemblance to native tissue. Current 3D loading platforms used in tendon mechanobiology are mostly based on collagen gel scaffolds; however, the integration between cells and the collagen gel is different from tenocytes with collagen fibers (31)(32)(33)(34). In our study, we generated 3D TDSC constructs by stimulating TDSCs to generate ECM, which closely mimics the binding between cells and the ECM in tendon tissue.…”
Section: Discussionmentioning
confidence: 99%
“…In pathological conditions, static compression stress activates excess TGFβ1819. In the physiologic state, TGFβ maintains chondrocyte homeostasis to preserve EP structure and function202122.…”
Section: Discussionmentioning
confidence: 99%